ACTUALIZATION OF ISLAMIC LAW IN MODERN LEGISLATION - Umar, Dr. H. (International Journal of Research -GRANTHAALAYAH, 2019)
Islamic law in the form of legislation in Indonesia is that which is legally binding on the constitution, even its binding capacity is broader. Therefore, as an organic regulation, sometimes it is not elastic to anticipate the demands of the times and change. For example, Law Number 1 of 1974 concerning Marriage. The law contains Islamic law and is binding on every citizen of the Republic of Indonesia. Problems that occur such as in Jambi Province at this time the fiqh law which is very broad in its scope is worthy of being called "Islamic law" is marriage law, inheritance law and waqf law. Laws or provisions that are applied to administer and settle marriages, inheritance and endowments as material laws, are still diverse. Marriage and Wakaf cases are regulated in statutory law; marriage is regulated by Law No. 1 of 1974 concerning Marriage and waqf law regulated by Government Regulation No.28 of 1977; as executor of the Agrarian Basic Law of 1961. Whereas inheritance law has not been regulated by law and by itself is still guided by Jurisprudence.